Estudo das interações entre a proteína TRF de Leishmania amazonensis (LaTRF) e suas possíveis parcerias - Ribeiro, João Augusto [UNESP] (2013)
Leishmaniasis is a spectrum of diseases caused by parasites of the genus Leishmania, affecting about 15 million people and exposing other 350 million that live in risk areas. Parasites have various mechanisms to maintain the integrity of its genome, among which is the maintenance of telomeres. Proteins belonging to the TRF (TTAGGG telomere repeat-binding factor) family form part of a multiprotein complex responsible for telomere maintenance in eukaryotes, including trypanosomatids. TRFs present a DNA binding domain, a homodimerization domain and regions that allow the protein to interact with other proteins. The aim of this project was to confirm the existence in Leishmania amazonensis telomeres of LaTRF protein partners, since preliminary results from our group revealed a possible complex formed with LaTRF, LaRPA-1 and LaRbp38. In order to obtain the LaTRF recombinant protein, we ordered the optimized gene sequence and its subcloning in the bacterial expression vector pQE-2 (QIAGEN). Recombinant LaTRF was expressed in low amount, but in soluble form. Circular dichroism spectroscopy analysis showed that the recombinant LaTRF was in its folded state and able to be used in vitro protein:protein interaction assays with its potential partners: LaRbp38 and LaRPA-1. Immunoprecipitation, indirect immunofluorescence and pull-down assays revealed that LaTRF physically interacts with LaRbp38 using a TRFH-docking like motif present in proteins that interact with the TRFs, such as TIN2 (TRF interacting factor 2). This suggests that LaRbp38, similarly to TIN2, may play a role of stabilizing LaTRF in double strand and promote the interaction of this complex with for example LaRPA-1, previously described as a protein that binds to the single stranded telomeric DNA. This possibly explains why LaTRF physically interact with LaRbp38 but not with LaRPA-1, although they all co-immunoprecipitated in the same complex. Here we describe ...